Localization of low-sulfur keratin proteins in the wool follicle using monoclonal antibodies (The Rockefeller University Press, 1986)
Monoclonal antibodies that recognize components of the low-sulfur keratin proteins extracted from Merino wool have been used to locate these components within the wool follicle. Immunoblotting procedures showed that all of the monoclonal antibodies bound more than one of the eight low-sulfur protein components, indicating that these proteins have antigenic determinants in common. Immunofluorescence studies showed that those antibodies specific for the component 7 family of the low-sulfur proteins bound to the developing wool fiber, whereas those antibodies recognizing the component 8 family bound to areas throughout the wool follicle, particularly the inner and outer root sheaths, but also to the fiber, the cuticle, and the epidermis. One of the monoclonal antibodies also bound to intermediate filament networks of cultured human epithelial cells.